Assessing the Environmental Impacts of Adventure Tourism in the World’s Highest Mountains: A Comprehensive Review for Promoting Sustainable Tourism in High-Altitude Areas - Zaheer AHMED; Takaaki NIHEI (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: Adventure tourism is where visitors participate in challenging and exciting activities in distant or exotic settings, such as rafting, trekking, and climbing, to experience adventure and challenge. This study explores the complex and diverse field of adventure tourism, with a particular emphasis on mountainous regions. Adventure tourism in mountainous regions has experienced remarkable growth, presenting challenges in environmental conservation, infrastructural development, safety, and socio-economic impacts. Methodology: Drawing on a comprehensive review of the literature and case studies, this study examines evolving adventure tourist preferences and activities while advocating for sustainable practices. It offers valuable insights for stakeholders to promote responsible tourism in mountainous terrains, encompassing activities like mountaineering, expeditions, and trekking. Additionally, the paper explores mountain landscapes’ global significance, tourism potential, and socio-economic benefits, addressing environmental challenges such as waste management and pollution. Findings: Emphasizing sustainable tourism’s aim to balance environmental, economic, and social factors, the study underscores the importance of minimizing negative impacts and maximizing community benefits. It highlights environmental impacts like habitat disturbance and pollution, economic benefits like income generation and job creation, and social impacts like community participation and cultural preservation. Implications/Novel Contribution: By adopting sustainable practices, tourism can contribute positively to destination development and local well-being. This study offers a deeper understanding of adventure tourism dynamics in mountainous regions and provides recommendations for sustainable development.